Preclinical Pharmacokinetics of MI-219, a Novel Human Double Minute 2 (HDM2) Inhibitor and Prediction of Human Pharmacokinetics - Peng Zou; Nan Zheng; Yanke Yu; Shanghai Yu; Wei Sun; Donna McEachem; Yongsheng Yang; Lawrence X Yu; Shaomeg Wang; Duxin Sun (Frontiers Media S.A., 2012)
Purpose. The two purposes of this study were evaluating preclinical pharmacokinetics of MI-219 and predicting clearance (CL) and volume of distribution at steady-state (Vdss) of MI-219 in humans. Methods. Pharmacokinetic studies were conducted on mice, rats, dogs, and monkeys. Human CL of MI-219 was predicted using allometric scaling (SA), multi-exponential allometric scaling (ME), rule of exponents (RoE), single species scaling, two-term power equation (TTPE), physiologically based in vitro-in vivo extrapolation (IVIVE), and fu corrected intercept method (FCIM). In vitro assays were conducted to determine in vitro intrinsic CL, protein binding, and blood-plasma partition coefficients. To estimate half-life of MI-219, plasma concentration-time profile in humans was predicted using kallynochron and apolysichron time transformation (Dedrick plots) and normalization with MRT and Vdss (Wajima's method). In addition, simultaneous interspecies scaling of CL, Vdss and concentration-time profile were performed by using Nonlinear Mixed Effects Modeling (NONMEM). Results. Preclinical studies showed that the elimination of MI-219 was mainly through metabolism. The validation using observed monkey CL and Vdss showed that MA, IVIVE and Oie-Tozer methods were accurately than the other methods. Human CL of MI-219 predicted by ME and IVIVE was between 0.237-0.342 L*h-1*kg-1. Human Vdss predicted by Oie-Tozer method and allometric scaling of unbound volume of distribution of tissues (VT/fuT) method was between 0.93-1.40 L*kg-1. Superimposition of rat, monkey and dog data was observed in Dedrick plots and Wajima's transformations. Conclusions. The predicted human pharmacokinetics is useful for the design of first-in-human study. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.